2015
DOI: 10.1063/1.4918360
|View full text |Cite
|
Sign up to set email alerts
|

Active and passive kink mode studies in a tokamak with a movable ferromagnetic walla)

Abstract: High-resolution active and passive kink mode studies are conducted in a tokamak with an adjustable ferromagnetic wall near the plasma surface. Ferritic tiles made from 5.6 mm thick Hiperco V R 50 alloy have been mounted on the plasma-facing side of half of the in-vessel movable wall segments in the High Beta Tokamak-Extended Pulse device [D. A. Maurer et al., Plasma Phys. Controlled Fusion 53, 074016 (2011)] in order to explore ferritic resistive wall mode stability. Low-activation ferritic steels are a candi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
3
6
0
Order By: Relevance
“…In the RWM theory, usually ferromagnetic effects are disregarded, which is justified by analytical and numerical analysis [84, 85] for slow modes. The situation is different for fast modes (at ) [86], which can be expected in future experiments in the JT-60SA tokamak [26] and, possibly in experiments with a movable ferromagnetic wall in the HBT-EP tokamak [87]. However, more often the results obtained with are good enough and can be easily extended to the area with [86].…”
Section: Boundary Conditionsmentioning
confidence: 99%
“…In the RWM theory, usually ferromagnetic effects are disregarded, which is justified by analytical and numerical analysis [84, 85] for slow modes. The situation is different for fast modes (at ) [86], which can be expected in future experiments in the JT-60SA tokamak [26] and, possibly in experiments with a movable ferromagnetic wall in the HBT-EP tokamak [87]. However, more often the results obtained with are good enough and can be easily extended to the area with [86].…”
Section: Boundary Conditionsmentioning
confidence: 99%
“…Given that the edge safety factor q is below 3 after 2.5 ms as shown in figure 7(a), and the mode has an m/n = 3/1 structureas shown by the SVD analysis of the PA array data during 3-5 ms in figure 7(c), this mode is categorized as a 3/1 XK. This kink mode saturates and persists without immediately disrupting the plasma, as is often seen in HBT-EP plasmas [33,34]. As shown in figure 8(a), the observed phase inversions in the temperature contour plots indicate the existence of a TM.…”
Section: Mode Analysis Of Sawtooth-suppressed Phenomenamentioning
confidence: 60%
“…Although FRWM effects have been observed in a linetied pinch [5], early ferromagnetic wall research in tokamak geometry demonstrated that breakdown performance was not impaired [6], and showed success in reducing the toroidal field (TF) ripple [7,8] with no observable reduction of the beta limit even in the presence of a complete ferritic first wall [7,9]. However, preliminary results on the High Beta Tokamak-Extended Pulse (HBT-EP) suggested accelerated mode growth and an enhanced rate of resonant magnetic perturbation (RMP)-induced disruption [10,11]. It was also found that a ferromagnetic wall increased demands on the MHD feedback control system [12].…”
Section: Introductionmentioning
confidence: 99%